2015
DOI: 10.1016/j.jcps.2015.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Looking for my self: Identity‐driven attention allocation

Abstract: This research builds on the motivational aspects of identity salience, finding that social identities direct the allocation of attention in identitysyntonic ways. Drawing from identity-based motivation (Oyserman, 2009;Reed, et al., 2012) we suggest individuals use attention to enhance identity-fit; selectively focusing on cues and stimuli that are identity-consistent. In two studies we find that activating a social identity drives preferential attention toward identity-relevant stimuli. Using a novel paradigm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
(77 reference statements)
0
27
0
Order By: Relevance
“…As discussed in a recent study , social disagreement could lead to less intense processing of the currently observed stimulus. Similar to the selective evasion of identity-and attitude-inconsistent information (e.g., Coleman & Williams, 2015;Oyserman, 2009), we might tend to tune down the intensity of our coding of objects associated with dissent. Clearly, future studies should address this issue more carefully.…”
Section: Social Deviance and Attentional Selectionmentioning
confidence: 97%
“…As discussed in a recent study , social disagreement could lead to less intense processing of the currently observed stimulus. Similar to the selective evasion of identity-and attitude-inconsistent information (e.g., Coleman & Williams, 2015;Oyserman, 2009), we might tend to tune down the intensity of our coding of objects associated with dissent. Clearly, future studies should address this issue more carefully.…”
Section: Social Deviance and Attentional Selectionmentioning
confidence: 97%
“…Consequently, ego development and differentiation are widely claimed to be the most important goals of human maturation (Mosig, 2006;Nitis, 1989;Walsh, 1988), leading to self-fulfillment that is considered synonymous with the good life (Chambers & Hickinbottom, 2008). Consumer researchers have endorsed these Western viewpoints on the self through a cornucopia of studies and reviews that go back over 50 years (see, e.g., Arnould & Thompson, 2005;Belk, 1988;Coleman & Williams, 2015;Escalas, 2012;Levy, 1959). Altogether, it is now thoroughly believed that consumption inherently transpires, and often succeeds, in the service of selfhood.…”
Section: Buddhism and The Three Marks Of Existencementioning
confidence: 99%
“…The women voluntarily stopped using these “existentially meaningful” possessions (Ahuvia, , p. 182) in public because they were incongruent with the identity prescribed for her by the abuser and attachment to these discrepant self‐symbolizing possessions would attract unwanted attention from him (Coleman & Williams, ). Thus, implicit in the concealment were both the self‐regulation practices of the women and the surveillance practices of their partners (Towns & Scott, ).…”
Section: Resultsmentioning
confidence: 99%